ApoE and outcome after traumatic brain injury. (October 2013) - Gokhale, Sankalp; Laskowitz, Daniel T
There is increasing evidence to support the role of genetic influences in determining functional outcomes in subjects with traumatic brain injury. In particular, apoE polymorphism has been identified as one of the important determinants of prognosis after traumatic brain injury (TBI). It is likely that apoE plays a central role in determining the neuroinflammatory response to various neurological injuries such as stroke, subarachnoid hemorrhage and TBI by modulating the function of microglia, which are a major source of inflammatory mediators in the CNS. There is evidence to support the role of apoE mimetic peptides as a novel therapeutic strategy in preclinical models of TBI. Ultimately, continued research focused on the interplay between lipid biology and acute brain injury responses may have the potential to define new neuroprotective strategies.